Hydro-mechanical modeling of borehole breakout in naturally fractured rocks using distinct element method. (September 2022) - Wei, Yaoran; Feng, Yongcun; Deng, Jingen; Li, Xiaorong
Abstract: Borehole breakout incidents in naturally fractured formations have plagued the petroleum drilling industry for decades. Borehole breakout is a progressive failure process controlled by multiple factors. Identifying the main factors that control borehole breakout is critical for successful drilling. This paper proposes a coupled geomechanics and fluid flow model for evaluating borehole breakout in fractured rocks, using a distinct element method. The model considers anisotropic drilling fluid invasion within natural fractures. The effect of in-situ stress, fracture density, fracture orientation, fluid dynamic viscosity, and joint strength on borehole breakout was investigated. The simulation results show that the fracture density dominates the yielded area around the borehole, while the direction of the fractures controls the shape of the breakout. With the increase of open-hole time and decrease in dynamic viscosity, the magnitude of borehole breakout increases due to increasing fluid invasion from the wellbore to the surrounding formation. The impacts of the above factors are demonstrated using numerical examples. Finally, some implications such as plugging fracture and using low permeability mudcake for preventing borehole breakout while drilling in naturally fractured formations are proposed based on the findings of this study. Highlights: A hydro-mechanical model for borehole breakout in fractured rocks was developed. The effect of various factors on borehole breakout was investigated. The density of natural fractures controls breakout magnitude. The orientation of natural fractures dominates the breakout shape.